Differential Effect of Hypoxia in Human and Mouse Vascular Smooth Muscle Cell Migration through LRP1-pPyk2-MMP-9 Axis. (19th May 2015) - Revuelta-López, E.; Castellano, J.; de Gonzalo-Calvo, D.; Nasarre, L.; Badimon, L.; Llorente-Cortés, V.
Abstract : LRP1-pPyk2 axis is essential for the upregulatory effect of hypoxia on MMP-9 activation and human VSMC (hVSMC) migration. Currently, there are not efficient models for the translational study of atherosclerosis. The morphological and physiological features of atherosclerosis are different between human and animal models, particularly in mouse models. Therefore, the aim of current investigation was to compare the effect of hypoxia on LRP1-Pyk2-MMP-9 axis in human and mouse vascular smooth muscle cells (mVSMC) and its consequences on VSMC migration. We demonstrated that hypoxic modulation of LRP1-pPyk2-MMP-9 axis is opposite between hVSMC and mVSMC. The modulation of LRP1/pPyk2 levels by hypoxia is positive in hVSMC but negative in mVSMC. We showed that the inverse effect of LRP1/pPyk2 axis is associated with a differential effect of hypoxia on MMP-9 expression and activation. Hypoxia-induced MMP-9 activation was concomitant with an increased hVSMC migratory capacity. Surprisingly, mVSMC migrate under hypoxic conditions despite the downregulatory effect of hypoxia on MMP-9 expression or activation. Our results highlight the crucial role of LRP1-pPyk2-MMP-9 axis in vascular cell migration. In addition, we propose that the extrapolation of results from animal models to humans is not suitable for this specific mechanism in hypoxia-related vascular conditions.